PEMANENAN AIR HUJAN SEBAGAI ALTERNATIF PENYEDIAAN AIR BERSIH DI DESA BANJARSARI, KABUPATEN TANGGAMUS - arniza FITRI; dian pratiwi; fajar dewantoro; fera Lestari (Journal of Social Sciences and Technology for Community Service (JSSTCS), 2022)
During the pandemic Covid 19, everyone washes their hands more frequently, so the need for clean water are increased. Since a few years ago, drought has become a fundamental problem in several areas in Indonesia, including in Banjarsari village, Tanggamus district, Lampung province. As we know, rain is one of the most widely available water sources in nature and can be accessed for free. Good management of rain can not only overcome the problem of water availability in the dry season, but can also overcome the problem of excess water in the rainy season and can also minimize the use of funds. Therefore, harvesting rainwater in Banjarsari village can be used as an alternative to reduce the problem of lack of clean water for villagers during the dry season for a low cost. In this PKM activity, the PKM team from Universitas Teknokrat Indonesia has successfully installed a rainwater harvesting unit at the residence of the Banjarsari sub-district head. Based on the information from the Banjarsari sub-district head, after several months of installing rainwater harvesting equipment at his residence, rainwater can be stored during the rainy season and can be used during the dry season so that it can help reduce the problem of lack of clean water in the village.